2006
DOI: 10.1016/j.polymdegradstab.2005.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of PEEK sheets under tensile stress

Abstract: The photochemical reaction of poly(ether ether ketone) (PEEK) sheets under tensile loads has been investigated. Two types of UV irradiation tests were carried out in a vacuum environment: with and without a cooling apparatus. Chemical structures, thermal properties, and mechanical properties were measured to clarify photo deterioration. Chemical analysis based on Fourier Transform Infrared Spectrometer (FT-IR) and X-ray Photoelectron Spectroscopy (XPS) showed photochemical scission caused by UV exposure. Therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 25 publications
3
26
0
2
Order By: Relevance
“…This observation is fully in line with Nakamura et al [10], who investigated PEEK after UVexposure using FTIR and found strong degradation of the polymer structure. Consequently, high-energy electromagnetic radiation, such as UV, is suggested as the main contributor to PEEK degradation.…”
Section: Solar Absorptancesupporting
confidence: 91%
“…This observation is fully in line with Nakamura et al [10], who investigated PEEK after UVexposure using FTIR and found strong degradation of the polymer structure. Consequently, high-energy electromagnetic radiation, such as UV, is suggested as the main contributor to PEEK degradation.…”
Section: Solar Absorptancesupporting
confidence: 91%
“…Table 5 shows the relative component percentages of the C 1s XPS high resolution spectra of all samples. The C 1s peak was fitted with peaks located at previously reported binding energies 26, 27. Peaks were located at 285 eV (CC/H), at 286.4 eV(CO/N), at 288.1 eV (CO) and 289 eV(COO/N).…”
Section: Resultsmentioning
confidence: 99%
“…Random chain scission at the ether and ketone linkages must occur first to generate stable radicals intermediates [33,34]. Dehydrogenation has been shown to be affected by thermal treatment [35,36], UV treatment [32,37,38], ion irradiation [31]. The relative decrease in the peak intensity at 1226 cm -1 and the relative intensity increase of peaks at 1653, 1599, and 1493 cm -1 observed in this work (peaks between zones 3 and 4, Figure 6) have been attributed to a change in chemical bonding due to plasma treatment [9] and melting [35,39].…”
Section: Analysis Based On Ftir Spectramentioning
confidence: 99%